Effects of 8-week of training on heart rate variability, overtraining state and performance in international young swimmers - Barragán, R.; González-Mohíno, F.; Veiga, S.; Santos-García, D. J. (Science & Sports, 2023)
The aim of this study was to determine the effects of different training periods and tapering during a macrocycle on heart rate variability (HRV), overtraining states and performance in young elite swimmers.